Performance of Some Promising Genotypes of Fine-flavour Cocoa Selected at Penataran Estate, East Java - Indah Anita Sari; Agung Wahyu Susilo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2014)
Prelimanary selection at Panataran Estate, East Java found five genotypes of promising fine flavor cocoa (PNT 12, PT 16, PNT 17, PNT 18, and PNT 33B) which had high yielding potency and estimated tolerant to VSD valuation of superior characters in each accession was important as base to be developed in multilocation test. The research was conducted in Penataran Estate, PTPN XII using single plot design and consisted of five fine flavor cocoa genotypes (PNT 12, PNT 16, PNT 17, PNT 18, and PNT 33B) and two genotypes as control (DR 2 and DRC 16). Each genotype consisted 33 plants (seven years old). Yield potential, score of VSD resistance, yield quality and morphology of stomata characters were observed. The analysis results showed that PNT 16 and PNT 12 had the highest of yield potential (1.46 and 1.10 kg/plant/year) respectively. PNT 16 also showed VSD scoring value low and stable on two years observation (2012-2013). Increasing pod number in 2013 was caused by recovery of the plant from VSD attack. Number of stomata on young leaf (flush) on PNT 16, PNT 17, PNT 18, and PNT 33B was lower than DR 2. Size of stomata qualitatively was different in each number. Characters of yield quality as pod lengh, pod weight, and pod girth on five promising clones were not as significantly different compared to control. Five fine flavor cocoa promising genotypes had white bean percentage more than 80 percent. Character of dry weight per bean on five fine flavour cocoa promising genotypes showed smaller than DR 2 but were not significantly different compared to DRC 16.